Protocol of a cluster randomised trial of BodyKind: a school-based body image programme for adolescents - Howard, Emma (My University, 2023)
Background Poor body image is prevalent among adolescents and associated with several negative outcomes for their physical and psychological health. There is a pressing need to address this growing public health con- cern, yet there are few evidence-informed universal programmes for older adolescents that address contemporary body image concerns (i.e., social media). BodyKind is a four lesson, school-based, teacher led, universal body image programme that incorporates empirically supported principles of cognitive dissonance, self-compassion, compas- sion for others and social activism, to support positive body image development. Building on previous pilot trials in the USA, this paper outlines the protocol for a cluster randomised control trial (cRCT) and implementation evalua- tion of the BodyKind programme which was culturally adapted for the Irish cultural context. Methods We aim to recruit 600 students aged 15-17 years in Transition Year (4th year) across 26 second-level schools in Ireland. Using minimisation, schools will be randomly assigned to receive BodyKind (intervention condition, n=300) or classes as usual (waitlist control, n=300). Teachers in intervention groups will receive training and deliver the programme to students over four weeks, at a rate of one lesson per week. Primary outcomes of body apprecia- tion, body dissatisfaction and psychological wellbeing and secondary outcomes of self-compassion, compassion for others, body ideal internalisation, social justice motives and appearance-based social media use will be assessed at pre-, post- and 2 month follow up. Mediation and moderation analyses will be conducted to identify how and for whom the intervention works best. An implementation evaluation will assess the quality of programme implementa- tion across schools and how this may influence intervention outcomes. Waitlist control schools will receive the pro- gramme after the 2-month follow up. Conclusion This study will be the first to implement a cRCT and an implementation evaluation to assess the impact of this multicomponent school-based body image programme designed to support healthy body image develop- ment. If shown to be effective, BodyKind will have the potential to improve adolescent body image and wellbeing and inform efforts to implement sustainable and scalable programmes in schools. Trial registration The trial was retrospectively registered on 10/10/2023 on ClinicalTrials.gov NCT06 076993.
PUBLISHED
Keywords: Implementation evaluation; Randomised control trial; Body dissatisfaction; Body image; Adolescent; Intervention; Protocol; School-based; Psychological wellbeing